2015
DOI: 10.2147/rru.s63448
|View full text |Cite
|
Sign up to set email alerts
|

Managing the adverse events of intravesical bacillus Calmette–Guérin therapy

Abstract: This paper provides recommendations on the management of complications arising from intravesical treatment with bacillus Calmette–Guérin (BCG) for nonmuscle-invasive bladder tumors. There is minimal recommendations currently available as randomized trials on the side effects of intravesical BCG are lacking and severe complications are usually described in case reports only. All physicians giving intravesical BCG should be aware of the possible complications that could arise and how to treat these. The incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
0
32
0
2
Order By: Relevance
“…In one report of 2600 patients treated with intravesical BCG, 27%-95% had symptoms of irritative lower urinary tract symptoms (LUTS), 2.9% with fever, 1.0% with hematuria and 0.4% with severe disseminated BCG sepsis [10] . In another study of 1316 patients, the reported BCG-induced cystitis was 35% and bacterial infection 23.3%, with frequency in 23.6%, and macroscopic hematuria in 22.6% [11] . The most frequent systemic side effects were general malaise in 15.5% and fever in 8.1% [11] .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In one report of 2600 patients treated with intravesical BCG, 27%-95% had symptoms of irritative lower urinary tract symptoms (LUTS), 2.9% with fever, 1.0% with hematuria and 0.4% with severe disseminated BCG sepsis [10] . In another study of 1316 patients, the reported BCG-induced cystitis was 35% and bacterial infection 23.3%, with frequency in 23.6%, and macroscopic hematuria in 22.6% [11] . The most frequent systemic side effects were general malaise in 15.5% and fever in 8.1% [11] .…”
Section: Discussionmentioning
confidence: 91%
“…In another study of 1316 patients, the reported BCG-induced cystitis was 35% and bacterial infection 23.3%, with frequency in 23.6%, and macroscopic hematuria in 22.6% [11] . The most frequent systemic side effects were general malaise in 15.5% and fever in 8.1% [11] . BCG sepsis was observed in four patients (0.3%) [11] .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Currently, due to the lack of randomized trials on the side effects of intravesical BCG, minimal recommendations are available, and severe complications are usually described in case reports only. 12 The suggested first-line treatment is the combination of isoniazid, rifampicin, and ethambutol. M. bovis is intrinsically resistant to pyrazinamide, and low-level isoniazid resistance has been described in some strains.…”
Section: Discussionmentioning
confidence: 99%
“…While it is usually well tolerated, local and systemic complications could occur (Liberek et al, 2006). Although these events are still uncommon, its varied range of clinical presentations and severity presents a challenge for the physicians, as they could occur even years after instillation (Decaestecker and Oosterlinck, 2015).…”
mentioning
confidence: 99%